Slavery and the Post-Black Imagination - Saal, Ilka; Ashe, Bertram D., 1959- (Book collections on Project MUSE., 2020)
"Slavery and the Post-Black Imagination brings the provocative category of post-blackness to bear on the past 30 years of artistic exploration into the afterlife of slavery as it continues to manifest in the United States. The selected essays cut across a broad spectrum of artistic media and genres -- including prose fiction, the graphic novel, verse, drama, film, TV, and music -- to capture the ubiquity and vibrancy of the post-black imagination in contemporary African American culture. They interrogate political, as well as formal, interventions into established discourses of slavery and black identities, to demonstrate how interrogations of black identities frequently goes hand in hand with the purposeful refiguration of slavery's prevailing tropes, narratives, and images. Taken altogether, this collection positions "post-blackness" as a valid and productive category of analysis that brings recent developments in African American cultural productions across variousmedia into sharp focus"--